Safety and efficacy of preoperative tranexamic acid in reducing intraoperative and postoperative blood loss in high-risk women undergoing cesarean delivery: a randomized controlled trial - Mohamed A. Shalaby; Ahmed M. Maged; Amira Al-Asmar; Mohamed El Mahy; Maged Al-Mohamady; Nancy Mohamed Ali Rund (BMC, 2022)
Abstract Background Objective to assess the value of preoperative tranexamic acid (TXA) in reduction of intraoperative and postoperative blood loss in high-risk cesarean delivery (CD). Methods A double blind randomized controlled trial included 160 high risk women who underwent elective lower segment CD. They were equally randomized to receive either 1 g of TXA or placebo 15 min before surgery. The primary outcome was Intraoperative blood loss. Results The estimated blood loss was significantly higher in the placebo group when compared to TXA group (896.81 ± 519.6 vs. 583.23 ± 379.62 ml, P < 0.001). Both postoperative hemoglobin and hematocrit were lower (9.2 ± 1.6 and 27.4 ± 4.1 vs. 10.1 ± 1.2 and 30.1 ± 3.4, P values < 0.001and 0.012 respectively) and their change percentages (15.41 vs. 7.11%, P < 0.001) were higher in the placebo group when compared to TXA one. The need for further ecbolics was higher in placebo group when compared to TXA group (46.25 vs. 13.75%, P < 0.001). Conclusion Preoperative TXA is safe and effective in reducing blood loss during and after high-risk CD. Trial registration ClincalTrial.gov ID: NCT03820206 .